Penerapan Metode MABAC pada Penentuan Coffee Shop Terbaik - Mohammad Aldinugroho Abdullah; Rima Tamara Aldisa (JURIKOM (Jurnal Riset Komputer), 2023)
The coffee shop business is a business engaged in services and transactions by trading drinks in the form of coffee. Opportunities regarding the habit of hanging out by the general public have motivated entrepreneurs to open a coffee shop business. The number of coffee shop businesses that exist today confuses connoisseurs of hanging out. The confusion arises because there are many existing coffee shop businesses so that people are ultimately confused about choosing the best coffee shop. To help people get confused about choosing the best coffee shop. For that we need an SPK. SPK is a system that is used to help the public or individuals or anyone who needs assistance in determining or making a decision regarding the selection of something. This SPK has a way of working that uses the same working method or is computer-based. SPK requires a method. The method used in this study is the MABAC method. This method is a method known as the main function, namely to find the best ideal solution. Based on the results of this study, the best alternative was obtained, namely the H6 alternative on behalf of Depression cafe with a value of 0.0875 as the best coffee shop recommendation